The Ritual Mamintak Ubek Padi Ka Jiraik Grave in Nagari Aia Gadang, Pasaman District, West Pasaman Regency - Nia Wahyuni; Yurisman; Hijratur Rahmi (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study discusses the meaning of The Ritual Mamintak Ubek Padi ka Jiraik Grave in Nagari Aia Gadang, Pasaman District, West Pasaman Regency. The background of the ritual of mamintak ubek padi originates from the community's fear of a disaster. This is because Nagari Aia Gadang is prone to flooding which causes the farming community to suffer losses. The purpose of this study is to find out the history and describe the procession and the meaning contained in the ritual of mamintak ubek padi ka jiraik's grave. This study uses a qualitative method with an ethnographic approach. Data collection techniques using observation techniques, interviews and documentation. The implementation of the ritual of mamintak ubek padi ka jiraik's grave must pay attention to the following: dress modestly, purify, prepare tools. When the ritual is carried out when the rice has begun to bear fruit by the people who need ubek rice from Jiraik's grave. The two stages of ubek compounding are: the ingredients that are used to make ubek are mixed and sprinkled on the rice in the fields and fields. Mamintak ubek padi ka jiraik graves for the community has the meaning that the rice fields or fields are protected from pests and diseases of rice plants and to get blessings from God through intermediaries of ancestral spirits.